Pengembangan model pengendalian internal berbasis framework COSO dalam konteks pesantren - Azwar, Ujang; Zakaria, Adam; Musyaffi, Ayatulloh Michael (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – This study aims to analyze the internal control conditions and weaknesses that occur in Islamic boarding schools, so that researchers can provide priority recommendations for improvement to mitigate the risks that occur. In addition, researchers developed internal controls from COSO so that they can be applied and understood by Islamic boarding school stakeholders in an easy, relevant, and effective manner. Methods – Project-based research was chosen in this study because it aimed to develop a model of internal control specific to Islamic boarding schools. The development used the 4D model, which consists of define, design, develop, and disseminate. Data were collected using observation, interviews, and documentation techniques. Meanwhile, the researchers used a risk matrix and triangulation techniques to process the data produced. Findings – This study produced two outputs: first, a SACICK (self-assessment checklist of internal control kits) evaluation guideline, which is useful for assessing the condition of internal control systems and mitigating risks; and second, recommendations for improvement in the form of a risk analysis report, which is useful as a database for mitigating risks in the following year. Implications – The implications of this research for Islamic boarding schools include the need to maintain, improve, supplement, and clarify categories in accordance with the internal control framework. Originality – This study differs from previous studies in terms of developing an internal control model that can be used to assess internal control conditions and mitigate risks.